Urban entrepreneurialism and the commodification of heritage in China. (November 2015) - Su, Xiaobo
This paper analyses urban entrepreneurialism in relation to the commodification of urban heritage in the context of China. The case study is Lijiang Old Town in Yunnan province. It is found that there are three markets through which profit is extracted from urban heritage: the tourist market, the real estate market and the capital market. These markets, ranging from simple to complex, reflect the Lijiang local government's innovative efforts to deepen the commodification of urban heritage and enhance local competitiveness. By discussing how profit is distributed, I argue that Lijiang's local government and its ruling elites have benefited more from tourist revenues than any other groups. An analysis of Lijiang's demographical displacement demonstrates that urban heritage is implicated in the complicated choices made by ordinary individuals in the face of political control and capital accumulation.